Effect of gymnastics on balance ability in children aged three to six years - Yu, Qiaoyan; Pan, Xiaofei; Liu, Zijing; Deng, Chenliang (Frontiers in Psychology, 2025)
ObjectiveThis study aims to explore the intervention effect of gymnastics movements on children’s balance ability.MethodsThe study selected 24 healthy children aged 3–6 years and randomly divided them into a control group and an experimental group for a 12 week experimental intervention. The experimental group conducted scientific gymnastics exercises, including proprioceptive training, single foot static balance training, and dynamic balance training; the control group maintained a normal sports lifestyle. Static and dynamic balance were assessed using methods from the National Physical Fitness Testing Standards Manual, and data were compared before and after the experiment.ResultsThe research results showed that the static and dynamic balance of the experimental group children were significantly improved, and the improvement effect was significantly better than that before the experiment and the control group (p<0.01). There was no significant difference in the control group before and after intervention (p>0.05), while there was a very significant difference in the experimental group before and after intervention (p<0.01). In addition, there is a difference in balance ability between boys and girls (p<0.05), with girls having better static balance ability and boys having stronger dynamic balance ability.Discussions and conclusions:The research conclusion is that long-term scientific gymnastics exercises can significantly improve children’s balance ability, and the effect is better than irregular physical exercise. It is suggested that government departments formulate policies to promote the promotion of gymnastics among young children. Schools should use gymnastics movements as the main method to improve children’s balance ability, and combine them with games to enrich teaching methods and attract children to participate. Parents should encourage their children to practice gymnastics or receive professional training while ensuring safety, in order to promote the healthy growth of young children. This study provides a scientific basis for improving children’s balance ability and enriches the value theory of gymnastics movements.